An experimental study on isotope fractionation in a mesoporous silica-water system with implications for vadose-zone hydrology. (1st July 2016) - Lin, Ying; Horita, Juske
Abstract: Soil water dynamics within a thick vadose (unsaturated) zone is a key component in the hydrologic cycle in arid regions. In isotopic studies of soil water, the isotopic composition of adsorbed/pore-condensed water within soils has been assumed to be identical to that of bulk liquid water. To test this critical assumption, we have conducted laboratory experiments on equilibrium isotope fractionation between adsorbed/condensed water in mesoporous silica (average pore diameter 15 nm) and the vapor at relative pressures p / po = 0.3–1.0 along the adsorption–desorption isotherm at 30 °C. The isotope fractionation factors between condensed water in the silica pores and the vapor, α ( 2 H) and α ( 18 O), are smaller than those between liquid and vapor of bulk water (1.074 and 1.0088, respectively, at 30 °C). The α ( 2 H) and α ( 18 O) values progressively decrease from 1.064 and 1.0083 at p / po = 1 to 1.024 and 1.0044 at p / po = 0.27 for hydrogen and oxygen isotopes, respectively, establishing trends very similar to the isotherm curves. Empirical formulas relating α ( 2 H) and α ( 18 O) to the proportions of filled pores ( f ) are developed. Our experimental results challenge the long-held assumption that the equilibrium isotope fractionation factors for the soil water–vapor are identical to those of liquid water–vapor system with potential implications for arid-zone and global water cycles, including paleoclimate proxies in arid regions.